Learning Strategies at SD Muhammadiyah 1 Krembung During Pandemic Covid 19 - Firdatus Nurlaila; Muhlasin Amrullah (International Consortium of Education and Culture Research Studies, 2021)
The purpose of this study was to describe learning in SD Muhammadiyah 1 Krembung. Starting from the impact of covid 19 on education at SD Muhammadiyah 1 Krembung, the history of the establishment of SD Muhammadiyah 1 Krembung, and learning at SD Muhammadiyah 1 Krembung in the covid 19 pandemic. The research method used was descriptive qualitative with research subjects namely the vice principal of SD Muhammadiyah 1 Krembung. Data collection techniques in this study through interviews, documentation, and observation. The impact of covid 19 on education at SD Muhammadiyah 1 Krembung is that students and teachers experience difficulties in teaching and learning, administrative problems (payments) that occur by parents of students, and obstacles with internet quotas. Muhammadiyah Elementary School was founded in 2015 with its founder, Mr. Sohib. The implementation of learning at SD Muhammadiyah 1 Krembung through bold and engaging learning. Bold learning is learning that uses the internet in learning. While offline learning is learning outside the network. Brave learning is carried out through whatsapp, youtube, zoom, and google meet groups. Meanwhile, learning attracts students to come to school. The time required for offline learning is 2 hours. From offline learning and offline learning, parents prefer offline learning because it is effective.